Fungal Planet description sheets: 1697-1780 - Crous, P W; Wingfield, M J; Jurjević, Ž; Balashov, S; Osieck, E R; Marin-Felix, Y; Luangsa-Ard, J J; Mejía, L C; Cappelli, A; Parra, L A; Lucchini, G; Chen, J; et al. (Fungal systematics and evolution, 2024)
Novel species of fungi described in this study include those from various countries as follows: Antarctica, Leuconeurospora bharatiensis from accumulated snow sediment sample. Argentina, Pseudocercospora quetri on leaf spots of Luma apiculata. Australia, Polychaetomyces verrucosus on submerged decaying wood in sea water, Ustilaginoidea cookiorum on Scleria levis, Xylaria guardiae as endophyte from healthy leaves of Macaranga tanarius. Belgium, Iodophanus taxi on leaf of Taxus baccata. Belize, Hygrocybe mirabilis on soil. Brazil, Gongronella irregularis from soil, Linodochium splendidum on decaying sheath of Euterpe oleracea, Nothophysalospora agapanthi (incl. Nothophysalospora gen. nov.) on flower stalks of Agapanthus praecox, Phaeosphaeria tabebuiae on leaf of Tabebuia sp., Verrucohypha endophytica (incl. Verrucohypha gen. nov.) from healthy roots of Acrocomia aculeata. Estonia, Inosperma apricum on soil under Quercus robur. Greece, Monosporascus solitarius isolated from surface-sterilised, asymptomatic roots of Microthlaspi perfoliatum. India, Diaporthe neocapsici on young seedling stems of Capsicum annuum, Fuscoporia naditirana on dead wood, Sebacina spongicarpa on soil, Torula kanvae from the gut of a Copris signatus beetle. Iran, Sarcinomyces pruni from twig and petiole tissues of Prunus persica and Prunus armeniaca, Xenodidymella quercicola from leaf spots of Quercus brantii. Italy, Agaricus aereiceps on grass, Agaricus bellui in meadows, Agaricus fabrianensis in urban grasslands, Beaucarneamyces muscorum on moss growing in forest, Xenoanthostomella quercus on leaf litter of Quercus ilex. Netherlands, Alfaria neerlandica on stem lesions of Cortaderia selloana, Neodictyosporium juncicola on culms of Juncus maritimus, Penicillium geertdesnooi from soil under Papaver rhoeas, Russula abscondita on rich calcareous soil with Quercus, Russula multiseptata on rich clay soil with Quercus, Russula purpureopallescens on soil with Populus, Sarocladium caricicola on leaves of Carex riparia. Pakistan, Circinaria shimlaensis on limestone rocks. Panama, Acrocalymma philodendri on leaf spots of Philodendron sp., Caligospora panamaensis on leaf litter, Chlamydocillium simulans associated with a Xylaria sp., Corynesporina panamaensis on leaf litter, Cylindromonium panamaense on twig litter of angiosperm, Cyphellophora panamaensis on twig litter of angiosperm, Microcera panamensis on leaf litter of fern, Pseudotricholoma pusillum in tropical montane forest dominated by Quercus spp., Striaticonidium panamaense on leaf litter, Yunnanomyces panamaensis on leaf litter. Poland, Albocremella abscondita (incl. Albocremella gen. nov.) from rhizoids of liverwort Conocephalum salebrosum. Portugal, Agaricus occidualis in meadows. South Africa, Alternaria elsarustiae on culms of unidentified Poaceae, Capronia capensis on dead twig of unidentified angiosperm, Codinaeella bulbinicola on dead leaves of Bulbine frutescens, Cytospora carpobroticola on leaf of Carpobrotus quadrifidus, Neophaeomoniella watsoniae on leaf of Watsonia sp., Neoplatysporoides aloigena on leaf of Aloe khamiesensis, Nothodactylaria comitabilis on living leaf of Itea rhamnoides, Nothopenidiella beaucarneae (incl. Nothopenidiella gen. nov.) on dead leaves of Beaucarnea stricta, Orbilia kirstenboschensis on dead flower stalks of Agapanthus praecox, Phragmocephala agapanthi on dead flower stalks of Agapanthus praecox, Podocarpigena hagahagaensis (incl. Podocarpigena gen. nov.) on leaf spots of Podocarpus falcatus, Sporisorium enterogonipteri from the gut of Gonipterus sp., Synnemapestaloides searsiae on leaf of Searsia populifolia, Xenophragmocapnias diospyri (incl. Xenophragmocapnias gen. nov.) on leaf spots of Diospyros sp., Yunnanomyces hagahagaensis on leaf spots of Sideroxylon inerme. Spain, Agaricus basicinctus in meadows, Agaricus quercetorum among leaf litter in oak forests, Coprinopsis palaciosii on degraded woody debris, Inocybe complutensis in calcareous loamy soil, Inocybe tanitiae in calcareous sandy soil, Mycena subfragosa on dead leaves of Salix atrocinerea, Pseudobaeospora cortegadensis in laurel forests, Trichoderma sedimenticola from fluvial sediments. Sweden, Inocybe badjelanndana on calcareous soil. Ukraine, Beaucarneamyces lupini on overwintered stems of Lupinus polyphyllus, Protocreopsis globulosa on thallus and apothecia of Lecania cyrtella on bark of Populus sp., Thyridium tiliae on dead twigs of Tilia sp. USA, Cladosporium louisianense, Cyphellophora americana from a bedroom vent, Extremus massachusettsianus from lyse buffer, Myxotrichum tapetae on carpet in basement, Neospissiomyces floridanus (incl. Neospissiomyces gen. nov.) on swab from hospital, Polychaetomyces marinus (incl. Polychaetomyces gen. nov.) on submerged driftwood in sea water, Steccherinum fragrans on hardwood fallen on the beach, Steinbeckomyces carnegieae (incl. Steinbeckomyces gen. nov.) on Carnegiea gigantea, Tolypocladium pennsylvanicum from air sampled in basement. Vietnam, Acidomyces ducanhii from Aglaia flowers, Acidomyces paludis from dead bark of Acacia sp., Phakopsora sageretiae on Sageretia theezans, Puccinia stixis on Stixis scandens. Morphological and culture characteristics are supported by DNA barcodes. Citation: Crous PW, Wingfield MJ, Jurjević Ž, et al. (2024). Fungal Planet description sheets: 1697-1780. Fungal Systematics and Evolution 14: 325-577. doi: 10.3114/fuse.2024.14.19.
Keywords: ITS nrDNA barcodes; LSU; systematics; new taxa